Critical thickness for the emergence of Weyl features in Co3Sn2S2 thin films - Junya Ikeda (Nature Portfolio, 2021)
The coexistence of ferromagnetism and topology has recently attracted intense interest. Here, the thickness dependence of magnetisation and anomalous Hall conductivity is investigated in Co3Sn2S2 thin films, revealing a critical thickness of 10 nm for the emergence of the magnetic Weyl semimetal phase.